The Netra Mandiri Foundation's Interpersonal Communication for Blind Tutors - Ilyas Ali Zainuddin; Sarah Afifah (Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2022)
This study discusses interpersonal communication for blind tutors at the Netra Mandiri Foundation in Palembang. This study aims to find out what factors affect interpersonal communication, how the process of interpersonal communication is, and how the impact of participants after attending classes at Yayasan Netra Mandiri Palembang. This research uses descriptive qualitative research. Methods of data collection include observation, interviews, and documentation. Based on the results of his study, the factors that affect interpersonal communication of the three subjects, AG, JK, and AP, can be seen in the second and fifth themes, namely about the point of view of the subject and other subjects. The interpersonal communication process of the three subjects, AG, JK, and AP, can be seen from the sixth and seventh themes on conveying material so that it is easy to understand and the material presented by the subject in class. The impact of the trainees participating in this training varied, including with subject training; they could easily do the online assignments given at their school, appear in cafes to become musicians and make bands, and be equipped to open massage services at home that they could help. The economy of the participants who took the training class. Impacts vary according to the aptitude of the trainees.